Karakteristik Habitat dan Konservasi Amfibi di Pulau Lombok - Muhammad Syazali; Agil Al Idrus; Gito Hadprayitno (Biota, 2019)
The previous study stated that there are 12 species of Amphibians found in Lombok Island, Indonesia. Four of which are the endemic species of Lesser Sunda Islands, namely Oreophryne monticola, Limnonectes kadarsani, Limnonectes dammermani dan Hylarana florensis. However, the information regarding the habitat characteristic which supports animal survival is limited. This study aimed to explore the types of habitat characteristics according to amphibian diversity in the Island of Lombok. The survey study was conducted at 9 locations (3 of habitat type) from March to July 2016. The collected data includes species composition and a sum of individuals of species. Amphibian diversity was analyzed using relative abundance and the Shannon-Wiener index. This study revealed that the nonforest habitat type was appropriate for five species, while secondary and primary forest habitat type was appropriate for seven species. Diversity of species index directly proportional to a natural level of habitat (H’ Nonforest = 1.3; H’ Secondary Forest = 1.7; H’ Primary Forest = 1.8). The highest species abundance was Bufo melanostictus (23.9%), and the lowest species abundance was Oreophryne monticola (0.9%). According to the distribution and relative abundance, the species that require conservation priorities are Oreophryne monticola and Hylarana florensis.